Right heart and left atrial strain to differentiate cardiac amyloidosis and Fabry disease - Isabel Mattig; Tilman Steudel; Karin Klingel; Gina Barzen; David Frumkin; Sebastian Spethmann; Elena Romero Dorta; Karl Stangl; Bettina Heidecker; Ulf Landmesser; Fabian Knebel; Sima Canaan-Kühl; et al. (Scientific Reports)
Abstract Echocardiographic differentiation of cardiac amyloidosis (CA) and Fabry disease (FD) is often challenging using standard echocardiographic parameters. We retrospectively analyzed the diagnostic accuracy of right heart and left atrial strain parameters to discriminate CA from FD using receiver operating characteristic curve analyses and logistic regression models. A total of 47 FD and 88 CA patients with left ventricular wall thickening were analyzed. The comparison of both cardiomyopathies revealed significantly reduced global and free wall longitudinal right ventricular strain (RVS; global RVS: CA − 13 ± 4%, n = 67, vs. FD − 18 ± 4%, n = 39, p < 0.001) as well as right atrial strain (RAS; reservoir RAS: CA 12 ± 8%, n = 70, vs. FD 26 ± 9%, n = 40, p < 0.001) and left atrial strain (LAS) in CA patients. Individually, global RVS as well as phasic LAS and RAS showed the highest diagnostic accuracy to distinguish CA and FD. The best diagnostic accuracy was achieved by combining the age, basal RV diameter, global RVS, and reservoir and conduit RAS (area under the curve 0.96 [95% CI 0.90–1.00]). Differential echocardiographic diagnostic work-up of patients with suspected CA or FD can be improved by integrating structural and functional parameters of the right heart and the left atrium. Trial registration: DRKS00027403.